Atomistic Simulation of Interstitial Dislocation Loop Evolution under Applied Stresses in BCC Iron. Issue 1 (7th November 2017) - Long, Xue Hao; Wang, Dong; Setyawan, Wahyu; Liu, Peng; Gao, Ning; Kurtz, Richard J.; Wang, Zhi Guang; Wang, Xue Lin
Abstract : Evolution of an interstitial 1/2 〈 111 〉 dislocation loop under tensile, shear, and torsion stresses is studied with molecular statics method. Under a tensile stress, the dependence of ultimate tensile strength on size of loop is calculated. The formation of small shear loops around the initial prismatic loop is confirmed as an intermediate state to form the final dislocation network. Under a shear stress, the rotation of a loop is observed not only by a change of the habit plane but also through a transformation between a shear and a prismatic loop. Under torsion, a perfect BCC crystal may undergo a BCC to FCC or BCC to HCP transformation. The present work indicates that a 1/2 〈 111 〉 loop can delay these transformations, resulting in the formation of micro‐crack on the surface. Abstract : Stress and torsion effect on evolution of interstitial dislocation loop. The tensile and shear stress effects are shown in (a) and (b). The torsion effect is shown in (c).